2007
DOI: 10.1021/jp074249f
|View full text |Cite
|
Sign up to set email alerts
|

Global Potential Energy Minima of (H2O)n Clusters on Graphite

Abstract: Likely candidates for the global potential energy minima of (H2O) n clusters with n ≤ 21 on the (0001) surface of graphite are found using basin-hopping global optimization. The potential energy surfaces are constructed using the TIP4P intermolecular potentials for the water molecules (the TIP3P is also explored as a secondary choice), a Lennard-Jones water−graphite potential, and a water−graphite polarization potential that is built from classical electrostatic image methods and takes into account both the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 36 publications
6
35
0
Order By: Relevance
“…2c and d, respectively. 52 The charge transfer analysis shows that each H 2 O donates about 0.035 e. The relatively large dipole moment of H 2 O induces a large charge redistribution even in the opposite side of the adsorbed phosphorene surface. (Fig.…”
Section: Molecular Donorsmentioning
confidence: 98%
“…2c and d, respectively. 52 The charge transfer analysis shows that each H 2 O donates about 0.035 e. The relatively large dipole moment of H 2 O induces a large charge redistribution even in the opposite side of the adsorbed phosphorene surface. (Fig.…”
Section: Molecular Donorsmentioning
confidence: 98%
“…Therefore, as the coverage increases, the cluster becomes more important, and a higher surface temperature is needed to desorb the molecules. Ab initio calculations from Lin et al (2005) and González et al (2007), determined the adsorption energies of a single water molecule, and to water molecules arrange as dimers, trimers, up to hexamers. These binding energies increase with the number of water molecules present in the cluster, but only if the cluster has two dimensions.…”
Section: Water Clustersmentioning
confidence: 99%
“…Motivated by potential technological applications, including water desalination, electricity generation, and biochemical sensing, there has recently been significant effort in investigating the properties of water interacting with graphene. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] From a computational modeling perspective, realistic simulations of water at the interface with graphene sheets require an accurate representation of the underlying molecular interactions, at both short and long ranges. Several molecular dynamics (MD) studies, employing either force fields or ab initio methods, have been reported to characterize the behavior of water adsorbed on graphene.…”
Section: Introductionmentioning
confidence: 99%